Borna disease virus infection in cats: ABCD guidelines on prevention and management. Issue 7 (July 2015) - Lutz, Hans; Addie, Diane D; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hartmann, Katrin; Horzinek, Marian C; Hosie, Margaret J; Lloret, Albert; Marsilio, Fulvio; Pennisi, Maria Grazia; et al.
Overview: Borna disease virus (BDV) has a broad host range, affecting primarily horses and sheep, but also cattle, ostriches, cats and dogs. In cats, BDV may cause a non-suppurative meningoencephalomyelitis ('staggering disease'). Infection: The mode of transmission is not completely elucidated. Direct and indirect virus transmission is postulated, but BDV is not readily transmitted between cats. Vectors such as ticks may play a role and shrews have been identified as a potential reservoir host. Access to forested areas has been reported to be an important risk factor for staggering disease. Disease signs: It is postulated that BDV may infect nerve endings in the oropharynx and spread via olfactory nerve cells to the central nervous sytem. A strong T-cell response may contribute to the development of clinical disease. Affected cats develop gait disturbances, ataxia, pain in the lower back and behavioural changes. Diagnosis: For diagnostic purposes, detection of viral RNA by reverse transcription PCR in samples collected from cats with clinical signs of Borna disease can be considered diagnostic. Serology is of little value; cats without signs of Borna disease may be seropositive and yet not every cat with BDV infection has detectable levels of antibodies. Human infection: A hypothesis that BDV infection may be involved in the development of selected neurological disorders in man could not be confirmed. A research group within the German Robert Koch Institute studied the potential health threat of BDV to humans and concluded that BDV was not involved in the aetiology of human psychiatric diseases.